Child Labor and Environmental Health: Government Obligations and Human Rights - Joseph J. Amon; Jane Buchanan; Jane Cohen; Juliane Kippenberg (International Journal of Pediatrics)
The Convention concerning the Prohibition and Immediate Action for the Elimination of the Worst Forms of Child Labour was adopted by the International Labour Organization in 1999. 174 countries around the world have signed or ratified the convention, which requires countries to adopt laws and implement programs to prohibit and eliminate child labor that poses harms to health or safety. Nonetheless, child labor continues to be common in the agriculture and mining sectors, where safety and environmental hazards pose significant risks. Drawing upon recent human rights investigations of child labor in tobacco farming in Kazakhstan and gold mining in Mali, the role of international human rights mechanisms, advocacy with government and private sector officials, and media attention in reducing harmful environmental exposures of child workers is discussed. Human rights-based advocacy in both cases was important to raise attention and help ensure that children are protected from harm.